Testing the Efficiency of the Canadian‐U.S. Exchange Market under the Assumption of no Risk Premium - LONGWORTH, DAVID (Journal of Finance, 1981)
ABSTRACT The efficiency of the Canadian‐U.S. exchange market for the current float is examined more extensively than previously. Semi‐strong‐form tests which admit the lagged spot rate as a predictor are considered in addition to the standard weak‐form test. These stronger tests reject the joint null hypothesis of an efficient exchange market and no risk premium for the period ending in October 1976, although not for the entire period. For almost every year the current spot rate provided a better forecast of the future spot rate than did the current forward rate.